PENELITIAN KARAKTERISTIK AERODINAMIKA TRAILING EDGE SIRIP ROKET PADA KECEPATAN TRANSONIK DENGAN SIMULASI NUMERIK - Aribowo, Agus (Indonesian Journal of Aerospace, 2005)
Research of fin aerodynamic at a speed of Transonik of importance remember at this speed regim rocket have strongly increas in coefficient of drag, where will cause negativety to attainment of altitude target or its dynamics stability. In general there is 3 fin type which is inverterate to be used by rockets of LAPAN. Third of him have been done by examination use simulation of CFD in 2-D compressible flow at a speed of 1.6 M to 2.4 M. From result of the research discovered behavioral phenomenon born embryo of shockwave at a speed of transonic in region of models B trailing edge cause direct to degradation of pressure and enlarge coefficient of drag.